Emotional Demands and Organizational Strategies in Managing Inclusive Educational Workplaces for Adolescents with asd - Razali, Geofakta; Putri, Sofia Tri (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to examine the level of emotional demands experienced by employees working in an inclusive educational setting for adolescents with Autism Spectrum Disorder (ASD), as well as to explore the organizational strategies implemented to support their emotional well-being. The research was conducted at London School Beyond Academy (LSBA), a vocational institution in Indonesia that focuses on the development of neurodivergent adolescents. Employing an explanatory sequential mixed method design, the study began with a quantitative survey using the Emotional Demands subscale from the Copenhagen Psychosocial Questionnaire (COPSOQ II), followed by semi-structured interviews with key personnel to explore their lived experiences and perceptions of institutional support. The quantitative results (N=40) revealed a moderate level of emotional demands (M = 14.42/20), indicating that emotional challenges were perceived as meaningful rather than overwhelming. Qualitative findings from thematic analysis further underscored this by revealing that emotional demands were often framed as professional calling and relational depth, although formal support systems remained underdeveloped. This study contributes to the literature on emotional labor in inclusive education by focusing specifically on neurodiverse vocational contexts, an area that remains underexplored in Indonesian educational research. The findings suggest that institutional strategies for psychological sustainability are essential not only for employee well-being but also for ensuring the long-term effectiveness of inclusive education models.